Efficiency of Financial Accounting System of the National Health Security Fund: Opinion from Accountant Personnel - Henprasert, Niramol; Pannarunothai, Supasit; Upakdee, Nilawan; Phanthunane, Pudtan (Journal of Health Science of Thailand, 2017)
This research and development was to improve efficiency of financial accounting system of the universal coverage scheme (UCS) of the National Health Security Office (NHSO) knowing that only a few hospitals were able to record the transferred fund correctly. The problem was partly stemmed from the practice of the cash-basis “financial document model”. This research conducted the first round of questionnaire survey in 2010 to heads of finance department in 398 hospitals followed with the second survey in 2011 to 414 hospitals after launching the new “ageing account model” to improve efficiency in financial process. In-depth interviews were employed to selected samples commenting the most and the least financial process improvements. The interviews were undertaken from November 2012 to February 2013. Respondents from surveys mentioned more efficient financial processes in terms of fund transfer, outstanding realization, speed and the ease of use of transferred fund, but less efficient in terms of the frequency of releasing reports. In-depth interviews confirmed that efficiency was interpreted as the quickness and correctness of fund transfer. Comparing efficiency of financial process of the UCS with other two government insurance schemes, the NHSO should improve timeliness and comprehensiveness of the ageing account model and benchmark with other schemes.